Iminodibenzyl induced redirected COX-2 activity inhibits breast cancer progression - Harshit Shah (Nature Portfolio, 2021)
Abstract Knocking down delta-5-desaturase (D5D) by siRNA or shRNA is a promising strategy to achieve 8-hydroxyoctanoic acid (8-HOA) production for cancer inhibition. However, the RNAi-based strategy to stimulate 8-HOA is restricted due to endonucleases mediated physiological degradation and off-target effects. Thus, to get persistent 8-HOA in the cancer cell, we recognized a D5D inhibitor Iminodibenzyl. Here, we have postulated that Iminodibenzyl, by inhibiting D5D activity, could shift the di-homo-gamma-linolenic acid (DGLA) peroxidation from arachidonic acid to 8-HOA in high COX-2 microenvironment of 4T1 and MDA-MB-231 breast cancer cells. We observed that Iminodibenzyl stimulated 8-HOA caused HDAC activity reduction resulting in intrinsic apoptosis pathway activation. Additionally, reduced filopodia and lamellipodia, and epithelial-mesenchymal transition markers give rise to decreased cancer cell migration. In the orthotopic breast cancer model, the combination of Iminodibenzyl and DGLA reduced tumor size. From in vitro and in vivo studies, we concluded that Iminodibenzyl could reprogram COX-2 induced DGLA peroxidation to produce anti-cancer activity.